Assessing the labour supply effect of harmonising regular retirement age in Austria - Benjamin Bittschi; Thomas Horvath; Helmut Mahringer; Christine Mayrhuber; Martin Spielauer; Philipp Warum (Austrian Institute of Economic Research (WIFO), 2024)
The aim of this study is to assess the impact of the ongoing harmonisation of the retirement age for women with that for men on women's labour supply in Austria. According to the current legal framework, the standard retirement age for women will be gradually raised from 60 to 65 years from 2024 onwards, with the retirement age being raised by 6 months each year. The impact of the pension reform on women's labour supply is quantified using the dynamic microsimulation model microDEMS. This model integrates demographic changes in line with official population projections and detailed labour market modelling. According to our projections, the labour supply of women aged 60 to 64 increases by 87,000 in 2040 compared to a scenario in which the retirement age remains unchanged. We compare our results with two alternative approaches: the more stylised microWELT simulation model and a purely data-driven approach. While all methods produce very similar results in the long run, the detailed modelling in microDEMS provides more plausible results during the transition period when the reform is gradually implemented. This is because it allows for a realistic representation of pension paths, taking into account all relevant pension types and the corresponding eligibility criteria, such as sufficient accumulated insurance periods. In contrast to a purely datadriven approach, microDEMS modelling also has the advantage of explicitly representing and quantifying the components of the change in labour supply.
Keywords: J26; C53; J21; 330; Dynamic microsimulation; pension reform; labour force participation